Privacy-preserving photo sharing framework cross different social network - Fenghua LI; Zhe SUN; Ben NIU; Jin CAO; Hui LI (Tongxin xuebao)
With rapid developments of digital photography and social networks,users of photo-sharing-supported social networking applications can easily forward photos across different social networks at the cost of their growing privacy concerns.To address this problem,a privacy-preserving photo sharing framework was proposed,which could apply to extended control and privacy invasion tracing.In extended control scheme,the following users on a dissemination chain was restrained by each user’s privacy policy.Then several privacy areas of photos were encrypted and the access control polices were bound to the uploaded photos,so that any privacy areas on the photos could be hidden away from unwanted viewers even across different social networks.On this basis,the behaviors of users were record by tracing scheme of privacy invasion,the integrality of records was protected by using nested signature algorithm.The correctness,security and performance of overhead of the scheme are then thoroughly analyzed and evaluated via detailed simulations.